Making the Social World without Words - Enrico Terrone (Rosenberg & Sellier, 2016)
I intend to criticize and amend one of the main theses of Searle’s social ontology, that is: the dependence of social reality on language. This thesis raises a circularity problem because, in Searle’s account, language has conventionality as an essential feature, but conventionality depends, on in turn, on social reality. I will argue that we can solve Searle’s circularity problem by considering forms of communication and ways of imposing normativity more fundamental than language.